Research infrastructure of green biomass application for self-sustaining local energy : (Tokyo University of Agriculture and technology, 2009)
This project aims to establish the research infrastructure of green biomass in Asia. Green biomass is expected to establish the self-sustaining local energy system by using various bioresources, climate and natural features, agricultural production technologies and rural society which are created and subsisted in Asis